Compression Behaviour of Intact Sintok Marine Clay - Mohammad, Muhammad Iqbal (Universiti Teknologi PETRONAS, 2021)
Geotechnical properties of marine clay from Sintok, Kedah have not been revealed in detail which might be helpful to get the range of allowable design range on this type of soil. There type of sample used to do testing in laboratory is intact samples. Scanning Electron Microscopy (SEM) is used to study the elements that have in the sample. Scanning Electron Microscopy is an extremely useful tool for studying the microfabric of engineering soils. This project aims to find the basic geotechnical properties of intact Sintok marine clay through testing such as particle size distribution (PSD), specific gravity, plastic limit and liquid limit test. Following that, onedimensional compression behaviour of marine clay was analysed and evaluated through the result from oedometer test. The preliminary insight of geotechnical properties of four intact marine clay samples from Sintok, Kedah were obtained and in general, they have quite similar in geotechnical classification. The marine clay samples were classified as well graded sand with silty clay. Based on the Casagrande chart, all marine clay samples were categorized in between of CL and CI, as having the degree of plasticity from low to intermediate and highly compressible. The elements can be concluded as almost similar for all samples with oxide, silicon and aluminium were the major elements.